Factors Influencing Accounting Fraud in Village Fund Management in South Kalimantan - Wanda Safitri; Novita WeningTyas Respati (Universitas Negeri Semarang, 2023)
Purpose: This study investigated the factors contributing to accounting fraud when handling village funds. The purpose of this study was to investigate and analyze how factors such as internal control systems, compliance with accounting regulations, personal morality, and information asymmetry in managing village funds are considered to influence accounting fraud. Method: Village officials and the Village Consultative Body at Tapin Selatan District, Kalimantan Selatan, were made up to be the study’s population. Purposive sampling was used in the sample selection process. One hundred twenty-six respondents served as the sample used in the analysis. The hypothesis was tested with multiple linear regression. Findings: Empirical evidence showed that accounting fraud was not affected by internal control systems. Another finding showed that compliance with accounting regulations and individual morality detrimentally impacted accounting fraud. On the contrary, accounting fraud is positively affected by asymmetric information. Novelty: The difference between this research and previous studies is related to the object studied, indicators on individual morality variables, and the addition of information asymmetry variables. Keywords: Accounting Fraud; Compliance with Accounting Regulations; Internal Control Systems; Individual Morality; Information Asymmetry